DAMPAK EKONOMI POLITIK KEBIJAKAN PENENGGELAMAN KAPAL DI INDONESIA - administratio Department; Tiara Novita; Noverman Duadji (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2017)
ABSTRACT. This research was discussed about the political economic impact of the shipscuttling policy in Indonesia, which dedicated that the Ministry of marine and Fisheries(KKP) in this far has not been maximal in carrying out the ship scuttling policy. There hasbeen focused in this research was about the ship scuttling policy with a whole inflicatedimpact based on the policy that has been implemented, to address the perpetrators ofillegal fishing who operates in the waters of fishery territorial republic of Indonesia(WPP-NRI). This research used the secondary research-type with the study of librarianshipapproach. There has constructivist perspective which involved with implemented it’spolicy. Researchers toot the conclusion that the ship scuttling policy didn't beenmaximize. There were still some obstacles that has not been handled effectively, humanresources have not been well distributed, facilities and infrastructure were not yetsufficient, and did’nt maximize the cooperation between the bilateral and multilateralinstitute, which involved in the implementation of the ship scuttling policy. From thereresearchers gave suggestion, (1) Overcoming the inflicted constraints effectivelly. (2)Created the well distribution of human resources in all of regions/regency/province,mainly in the sea border. (3) Adjust the facilitiest and infrastructure needed as well asstrengthen the cooperation relation with stakeholders are involved. Keywords: Impact, Political Economy, Policy